CRITICAL STUDY ON THE FALLACIES OF H.A.R. GIBB’S VIEW ON MODERNITY OF ISLAMIC THOUGHT - Rahmansyah, Imam Toriqor (Spektra: Jurnal Ilmu-ilmu Sosial, 2021)
Talking about modernization, modernism, modernity, especially modernity of Islamic thought (al-tajdid) is a matter of serious discussion. These all are western terminologies which were adopted by Muslim modernists into Islamic tradition, and then by the adoption above, contradiction extremely appeared among them. To be noted some of modern thinkers who thought that the traditional interpretation of Islam does not satisfy many people who have received modern education. Some of these modern thinkers go to extreme and would like to exclude all worldly affairs from the purview of Islam. But, if this is done, Islam will lose all its distinctiveness and superiority. In most cases, according to western society the term modernity, modernization, meant to modernize the idea, ideology, trend and to modify the old tradition, form institutions and etc, and then an adjustment to the new situation which created by science development and modern western technology